The Impact of Culture and Employee-Focused Criteria on Productivity: A Structural Equation Modelling Approach - M. R., Abdul Hamid; Zainol, Mustafa; Nur Riza, Mohd Suradi; Fazli, Idris; Mokhtar, Abdullah (AIP Publishing LLC, 2012)
Culture and employee-focused criteria are important factors for the success of any organization. These factors have to be aligned with the productivity initiatives in the organization in order to gear ahead for excellence. Therefore, this article investigated the impact of culture and employee-focused criteria on productivity in Higher Education Institutions (HEIs) in Malaysia using intangible indicators through core values. The hypothesized relationship was tested the target population. The results of the modelling revealed that the PLS estimation confirmed all the hypotheses tested as in the hypothesized model. The results generally support significant relationships between culture values, employeefocused values and productivity-focused values. The study also confirmed the mediating role of employee-focused values for the relationship between culture values and productivity-focused values. In conclusion, the empirically validated results supported the adequacy of the hypothezised model of the impact of culture and employee-focused criteria on productivity in HEI through value-based indicators.